A lateral flow strip based on gold nanoparticles to detect 6-monoacetylmorphine in oral fluid. Issue 6 (27th June 2018) - Liu, Jia; Hu, Xiaolong; Cao, Fangqi; Zhang, Yurong; Lu, Jianzhong; Zeng, Libo
Abstract : We used lateral flow strips based on gold nanoparticles to detect 6-monoacetylmorphine (6-MAM; heroin's unique metabolite) in oral fluid samples. In this competitive lateral chromatographic immunoassay, the 6-MAM was chemically synthesized and conjugated to bovine serum albumin. The results were qualitatively detected via the colour change of the test line. By using a proper sample pad, a suitable nitrocellulose membrane and a customized sponge device adsorbed the oral fluid directly from the mouth; the total test time was 3 min. The sensitivity of the assay was 4.0 ng ml −1 without any cross-reactivity with 10 normal drugs, which are widely subject to abuse, including morphine and codeine. This test could be easily used on site to detect heroin in oral fluid, and it could be a promising product in the future including for driving under the influence.